An impedance-based diameter gauge for in-pile fuel deformation measurements. Issue 6 (2nd November 2019) - Fleming, Austin; Al Rashdan, Ahmad; Jensen, Colby; Calderoni, Pattrick
Abstract: During irradiation, the fuel-cladding interface of a nuclear fuel rod can experience significant mechanical and chemical interaction. In-situ measurement of the radial deformation of the cladding can quantify the extent of this interaction and the state of the cladding. Existing capabilities to perform in-pile diameter measurements are limited by required contact and an intrusive presence of a device near to a specimen. To overcome these limitations, researchers have developed and evaluated an electrical impedance based diameter gauge using a benchtop system. The sensor consists of an electrically conductive concentric ring around the fuel cladding such that the electrical impedance between the ring and cladding is measured. The cladding diameter is determined through a measurement of the electrical impedance between the electrodes with a known ring electrode diameter. Analytic and three-dimensional finite element analyses (FEA) were used to quantify the measurement sensitivity, uncertainty, and off-design conditions. The experimental sensor measured diameters with less than 20 μm of error, and had a measurement resolution of less than1 μm for diameters ranging from 9.5 to 9.6 mm. The uncertainty analysis for the experimental setup estimated an uncertainty of 20 μm, consistent with the experimentally measured results.